Kultivasi Bawang Merah Ramah Lingkungan di Wilayah Berpasir Spesifik di Yogyakarta - SUTARDI, .; PORWONINSIH, HENI (Departemen Biologi, Institut Pertanian Bogor, 2018)
Shallot is one of strategic commodities in Indonesia. Sandy coastal area of Bantul and Kulon Progo districtis the centre of shallot production in Yogyakarta. The results showed that recommendation of fertilizing technology ameliorant (clay 2:1), organik fertilizer 20 ton/ha, Urea 115.7 kg/ha, ZA 250 kg/ha, SP-36 75 kg/ha, and KCl 250 kg/ha. Pest and disease management in integrated pest and disease management 10 Feromon – Exi, Attractant, 10 Light trap, 45 Yellow/white/green trap, biopesticide, limited chemical pesticide, organophosphate pesticide residue contents below with residues below the MRL